Nutrient Composition of Two Edible Indonesian Marine Seaweeds from Binuangen Coast, Banten - Lili Indrawati; Nugroho Abikusno; Thamrin Wikanta (Fakultas Kedokteran Universitas Kristen Indonesia, 2016)
Abstract Indonesia has a potency to be the biggest producer of seaweed in the world but most of the seaweeds are underutilized and their health benefits are unknown. Seaweeds can be a very interesting natural source of new compounds with biological activity. This study was conducted to create a nutritional data for two species of seaweeds commonly found in Binuangen coast of south Banten in order to popularize its consumption and utilization. The proximate composition, minerals, protein, fat, carbohydrate profiles of two tropical edible seaweeds, Ulva fasciata and Rhodymenia palmata, were studied. The protein and carbohydrate content of seaweed were 11.55-17.61 g/100 g and 24.23-25.90 g/100 g dry weight (d.w.) respectively. The seaweeds were low in lipid content on dry weight basis. These seaweeds contain 7.98-11.01% macro-minerals (Na, K, Ca and Mg) and 695.48- 2048.19 ppm trace elements (Fe, Zn, Cu, and Mn). These seaweeds are nutritionally valuable thus making them a potential health ingredient for use as nutrition. Keywords: nutrient composition, U. fasciata, R. palmata, Binuangen beach, Banten Abstrak Indonesia mempunyai potensi untuk menjadi produsen rumput laut terbesar di dunia tetapi sebagian besar tumbuhan tersebut masih belum dimanfaatkan dan manfaatnya untuk kesehatan belum banyak diketahui. Rumput laut adalah sumber bahan alami yang memiliki aktivitas biologis. Penelitian ini bertujuan mengetahui data kandungan gizi dari dua spesies rumput laut yang banyak ditemukan di pantai Binuangen, Banten dalam rangka mempopulerkan penggunaannya sebagai nutrisi di Indonesia. Profil mineral, protein, lemak dan karbohidrat dari dua jenis rumput laut yang biasa dikonsumsi, yaitu Ulva fasciata dan Rhodymenia palmata dianalisis. Kandungan protein dan karbohidrat rumput laut tersebut berkisar 11,55-17,61 g/100 g dan 24,23-25,90 g/100 g berat kering. Rumput laut tersebut mengandung lemak yang rendah, mengandung 7,98-11,01% mineral makro (Na, K, Ca dan Mg) dan 695,48- 2048,19 ppm elemen renik (Fe, Zn, Cu, dan Mn). Kandungan gizi kedua rumput laut tersebut bermanfaat untuk menjadi bagian nutrisi. Keywords: kandungan gizi, Ulva fasciata, Rhodymenia palmata, pantai Binuangen, Banten